Funcionalidade do assoalho pélvico de idosas fisicamente ativas - Vey, Ana Paula Ziegler (2016)
The lower urinary tract undergoes changes with increasing age may result in disorders such as reduced bladder capacity and decreased ability to postpone the urination. Studies aimed at the pelvic floor and the level of physical activity of older women are still scarce. The aim of this study was to analyze the functionality of the pelvic floor active older women physically. This was a descriptive study of quantitative type. Were the sample inclusion criteria: women aged 60 or older, preserved cognitive function, as measured by the Mini Mental State Examination, with functional independence measured by the Katz scale. The sample consisted of 51 elderly, with a mean age of 67.8 (± 5.2) years participating in a university extension program of a public university in southern Brazil. It used as research tools to diagnostic sheet with identification data, sociodemographic characteristics, health conditions, urogynecologic aspects and regular physical activity, through the interview and functional evaluation of the pelvic floor, made through the PERFECT scheme . The evaluation of the physical activity level was accomplished through the use of the accelerometer for seven days a week. The variables studied in this research were analyzed descriptively through measures of central tendency (mean and standard deviation, median, according to the nature of the data) and simple frequency and percentage. To compare the pelvic floor functionality (PERFECT Scheme) and its components (strength, endurance, repetition number of slow contractions and rapid contractions) with the physical activity of older test was used one-way ANOVA. The significance level was 5%. It stands in the old marital status of widows (43.1%), living with family members (43.1%), with schooling from 5 to 8 years of education (43.1%), catholic (78 4%), retired (33.3%) and family income between 1 and 2 minimum wages (43.1%). Older practice physical activity on average for 10 (± 9.24) years, two (2) times a week. Most older does not practice other physical activity apart from the data in the university program. The median of the pelvic floor components were: 3 to force, 2 seconds for strength, 3 and 4 to repeat for fast fibers. It follows that although the pelvic floor strength is considered good, there is no relationship of physical activity in counts per minute and pelvic floor function, which demonstrates that the older group is very homogeneous in terms of these variables.